2020
DOI: 10.1002/jcop.22485
|View full text |Cite
|
Sign up to set email alerts
|

A human diversity analysis of culture and gender in Asian American men's intimate partner violence perpetration

Abstract: This integrative literature review aims to fill the gap in our understanding of the cultural and gendered predictors of intimate partner violence (IPV) perpetration by Asian American men. A comprehensive search using PsycINFO returned N = 24 peer-reviewed journal articles that examine Asian American men's IPV perpetration and patriarchal gender role norms and that met inclusion criteria. Patriarchal gender role norms consistently predicted IPV perpetration. However, the associations between acculturation/encul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…IPV is a significant public health issue affecting human beings. IPV has received widespread attention in the West, especially in the United States [ 13 , 16 , 21 , 22 , 23 ]. These studies found that different types of IPV are related to age, relationship status, family income, residential area, and childhood violence [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…IPV is a significant public health issue affecting human beings. IPV has received widespread attention in the West, especially in the United States [ 13 , 16 , 21 , 22 , 23 ]. These studies found that different types of IPV are related to age, relationship status, family income, residential area, and childhood violence [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%